Perception of Urban Consumers on Dairy Farming and Milk Consumption in North India - Mondal, Indrajit; Bhandari, Gunjan; Sen, Biswajit; Panja, Amitava (Indian Journal of Extension Education, 2022)
Increasing commercialization of dairy farming, diversity of products, consumer awareness and unlimited access to various information might have influenced the perception of consumers which finally affect their purchasing behaviour. Present study attempts to study the perception of consumers on dairy farming and milk consumption by analysing primary data collected from 270 milk consuming households using a Perception Index constructed for the purpose. The overall perception index was estimated to be 68, indicating that consumers have a favourable perception of milk consumption and dairy farming. Consumer households had higher positive perception on nutrition and health effects of milk (79.33) and economic benefits of dairy farming (77.56). However, they were concerned about milk safety (53.54) and ethical aspects (57.03). Stringent quality control, inspection and monitoring are required for ensuring safe milk so that the apprehensions in the mind of consumers can be removed. Efforts also needs to be directed towards animal welfare.
Keywords: Milk consumers; Perception index; Milk safety; Ethical concerns